Unsettling: Jews, whiteness, and incest in American popular culture - Bromberg, Eli (Rutgers University Press, 2020)
"By analyzing how various media told stories about Jewish celebrities and incest, Unsettling illustrates how Jewish community protective politics impacted the representation of white male Jewish masculinity in the 1990s. Chapters on Woody Allen, Roseanne Barr, and Henry Roth demonstrate how media coverage of their respective incest denials (Allen), allegations (Barr), and confessions (Roth) intersect with a history of sexual antisemitism, while an introductory chapter on Jewish second-wave feminist criticism of Sigmund Freud considers how Freud became "white" in these discussions. Unsettling reveals how film, TV, and literature have helped displace once prevalent antisemitic stereotypes onto those who are non-Jewish, nonwhite, and poor. In considering how whiteness functions for an ethno-religious group with historic vulnerability to incest stereotype as well as contemporary white privilege, Unsettling demonstrates how white Jewish men accused of incest, and even those who defiantly confess it, became improbably sympathetic figures representing supposed white male vulnerability"--